1997
DOI: 10.1002/anie.199717141
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Pentalene and Methylpentalene Complexes of Titanium, Zirconium, and Hafnium

Abstract: In the compounds 8a, 8b, and 8 d the vanadium atom has a distorted pseudo-trigonal geometry. The magnitudes of the angles DI-V-D2 and Dl-V-D3 differ only slightly (148-152"), as of necessity do those of D2-V-D3 (59-61"). The V-C bond lengths within the vanadium-Cp and vanadium-Cp* moieties lie between 2.20 and 2.26 A and in all cases V-D1 is 1.89 A. The most prominent structural feature of the new vanadium complexes 8 is the strong folding of the pentalene or methylpentalene ligand towards the metal atom along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 28 publications
9
65
0
Order By: Relevance
“…For example, the mononuclear tantalum(V) complexes (η 8 -Pn † )TaClxMe3-x for x = 0-3, which show a small but discernable increase in FA as the number of electron withdrawing chloride ligands increases. [15] Furthermore, the electronic properties of the pentalene ligand itself have an effect on FA, as first shown by comparison of the FAs for (η 8 -Pn)ZrCpCl (33.0°) [16] and (η 8 -Pn*)ZrCpCl (30.7°), [14,17] which provides evidence for the enhanced donor ability of the permethylated ligand.…”
Section: Structural Studies Of η 8 -Pentalene Complexesmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the mononuclear tantalum(V) complexes (η 8 -Pn † )TaClxMe3-x for x = 0-3, which show a small but discernable increase in FA as the number of electron withdrawing chloride ligands increases. [15] Furthermore, the electronic properties of the pentalene ligand itself have an effect on FA, as first shown by comparison of the FAs for (η 8 -Pn)ZrCpCl (33.0°) [16] and (η 8 -Pn*)ZrCpCl (30.7°), [14,17] which provides evidence for the enhanced donor ability of the permethylated ligand.…”
Section: Structural Studies Of η 8 -Pentalene Complexesmentioning
confidence: 92%
“…Bis(pentalene) sandwich compounds where the pentalene ligand is octohaptic have been characterised for Ti, Zr, Hf, [16] Ce [22,23] Th [20] and U. [20,21] The d-block Group 4 M(η 8 -Pn)2 compounds lack X-ray structural data but low temperature NMR studies suggest a D2 structure.…”
Section: Bis(η 8 -Pentalene) Compoundsmentioning
confidence: 99%
“…23 Due to the incipient nature of pentalene titanium chemistry, Cp remains the only carbon based ligand to be incorporated into any ''PnTi''-fragment. 19 27,28 Herein we report the synthesis and characterisation of the first Pn*Ti dialkyl complexes and investigate their subsequent reactivity with CO 2 .…”
mentioning
confidence: 99%
“…Again similar to MCp chemistry, Jonas et al reported that [Li 2 (DME) x ]Pn would react cleanly with Cp 2 VCl by substitution of one Cp − ligand and chloride. 58 The resulting η 5 CpVη 8 Pn complex (Fig. 34) is air sensitive but could be sublimed under vacuum to give pure product in high yields.…”
Section: Pentalenide Complexes Through Transmetalation Of Pentalenidesmentioning
confidence: 99%